Human keratinocyte sensitivity towards inflammatory cytokines varies with culture time - G. Elliott; D. van de Meent; J. van Dijk; M. Mol (Mediators of Inflammation)
Proliferating keratinocyte cultures have been reported to synthesize higher concentrations of prostaglandin (PG) E than confluent ones. As interleukin-1 (IL-1) stimulates keratinocyte PGE synthesis we investigated whether the degree of confluency of the keratinocyte culture modified the response of the cells to IL-1. It was found that IL-1α (100 U/ml) stimulated PGE2 synthesis by proliferating (7 days in culture) but not differentiating (14 days in culture) keratinocytes. Similar effects were observed using tumour necrosis factor-α. Both arachidonic acid (AA) and the calcium ionophore A23187 stimulated PGE2 synthesis by 7 and 14 day cultures although the increase was greatest when 7 day cultures were used. Our data indicate that there is a specific down-regulation of the mechanism(s) by which some inflammatory cytokines stimulate keratinocyte eicosanoid synthesis as cultured keratinocytes begin to differentiate.